Proteomics analysis reveals novel insights into the mechanism of hepatotoxicity induced by Tripterygium wilfordii multiglycoside in mice - Miao, Yingying; Zhang, Qin; Yuan, Zihang; Wang, Jie; Xu, Yunxia; Chai, Yuanyuan; Du, Min; Yu, Qinwei; Zhang, Luyong; Jiang, Zhenzhou (Frontiers in Pharmacology, 2022)
Tripterygium wilfordii multiglycoside (GTW), extracted and purified from the peeled roots of Tripterygium wilfordii Hook.f. (TwHF), is a well-known traditional Chinese medicine and applied to various autoimmune diseases clinically. However, it has been reported to cause severe liver injury. At present, the mechanism underlying GTW-induced hepatotoxicity remain poorly defined. Here, we evaluated the effects of GTW on mouse liver and elucidated the associated mechanisms via label-free proteomics combined with bioinformatics analysis. Male C57BL/6J mice were randomly divided into normal group, a low-dose GTW (70 mg/kg) group and a high-dose GTW (140 mg/kg) group. After one-week administration, GTW dose-dependently induced hepatotoxicity. Further analysis showed that GTW could act on the intestinal immune network for IgA production pathway, which plays an important role in maintaining intestinal homeostasis and influences the crosstalk between gut and liver. Western blots confirmed that GTW could decrease pIgR protein expression in the liver and ileum, and, as a result, the secretion of IgA into gut lumen was reduced. Further validation showed that intestinal barrier integrity was impaired in GTW-treated mice, promoting bacteria transferring to the liver and triggering proinflammatory response. Our study demonstrated that gut-liver axis may play a vital part in the progression of GTW-induced hepatotoxicity, which provides guidance for basic research and clinical application of GTW.